Recycling in Polymer Additive Manufacturing : A review of recycling methods and their impact on thermomechanical properties of polymers - Hanski, Tatu (My University, 2024)
Polymer material production is increasing yearly, and improvements for polymer waste management are required. Polymer additive manufacturing uses thermoplastic materials, which means that they can be obtained through the common recycling methods for polymers. Recycling supports circular economy, and economical and ecological advantages can be found by using recycled feedstock in additive manufacturing instead of using raw materials. In this thesis, a literature review was conducted to present ways to recycle polymer waste into feedstock for polymer additive manufacturing. Polymer recycling processes are mechanical, thermal, and chemical. Mechanical recycling is cheaper and easy to implement, but it is unable to remove impurities from the polymer waste. Chemical and thermo-chemical recycling is able to remove impurities, but it is generally more expensive and energy-consuming to use when compared to mechanical. Recycling generally decreases thermomechanical properties of polymers, which can cause problems in both the mechanical properties of the printed parts, and the printability of the recycled polymer feedstock. There are available solutions to decrease the thermomechanical degradation of the recycled polymer, which increases the usability of the recycled feedstock in additive manufacturing. For example, virgin polymer material can be added to the recycled polymer before the re-extrusion, which is a relatively cheap way to increase the thermomechanical properties. It is suggested that large-format additive manufacturing should be considered when using recycled feedstock. The large-format additive manufacturing printing process is less likely to fail due to small inconsistencies in the feedstock, and a larger printing area allows the printing layer to cool down more before another layer is added, which increases the interlayer fusion. A need for standardization of recycling was found in additively manufactured polymer parts, such as already exists with polymer parts made with conventional manufacturing methods.

Polymeerintuotanto kasvaa vuosittain, minkä vuoksi parannuksille polymeerijätteen käsittelyssä on kasvava tarve. Polymeeria käyttävä lisäävä valmistus käyttää lämpömuovattavia polymeereja raaka-aineena, joten raaka-ainetta voidaan saada polymeerin kierrätysmekanismeja hyödyntämällä. Kierrättäminen kannattaa kiertotaloutta, minkä lisäksi kierrätetyn materiaalin käyttö uuden raaka-aineen sijaan antaa muita ekologisia sekä taloudellisia etuja. Tämä tutkielma on kirjallisuuskatsaus, joka esittää tapoja yhdistää kierrättäminen ja lisäävä valmistus ja polymeerin kierrätyksen vaikutuksesta tulostettavuuteen. Polymeerin kierrätyskeinot voidaan jakaa mekaanisiin, lämpö-, kemikaalikierrätystekniikoihin. Mekaaninen kierrätys on edullisin keino, mutta sen avulla ei pystytä poistamaan epäpuhtauksia muovijätteestä. Lämpö- ja kemikaalikierrätys on tyypillisesti kalliimpaa ja energiaintensiivisempää, mutta molemmilla tavoilla pystytään poistamaan epäpuhtauksia polymeeristä. Kierrätyksen huonoja puolia ovat kuitenkin sen vaikutukset polymeerimateriaalin ja siitä tuotetun kappaleen termomekaanisiin ominaisuuksiin, huonontaen samalla sen 3D-tulostettavuutta. Termomekaanisten ominaisuuksien huononemista voidaan estää tai vähentää erilaisin keinoin, esimerkiksi lisäämällä uutta raaka-ainetta kierrätetyn materiaalin sekaan. Suuren tulostusalueen lisäävää valmistusta pidetään myös hyvänä tapana pienentää tulostettavuusongelmia kierrätetyn polymeerin tilanteessa. Suurempi tulostin on vähemmän herkkä materiaalin pieniin epäjatkuvuuskohtiin, ja suurempi tulostusalue antaa enemmän kerroksen jäähtymiselle ennen uuden kerroksen lisäämistä, kasvattaen kerrostenvälistä fuusiota. Lisäävän valmistuksen tuotteiden kierrätysmerkinnöille on tarve standardisoinnille, jota löytyy tavanomaisesti valmistetuista polymeerituotteista.
Keywords: Additive manufacturing, recycling, polymer